Machine perfusion in liver transplantation: highlights from the International Liver Transplantation Society Congress 2025 - Putri, Aghnia Jolanda; Singh, Jessica; Felgendreff, Philipp; Czigány, Zoltán; Martins, Paulo N. (Artificial organs, 2025)
This manuscript synthesizes the most recent advances in machine perfusion (MP) presented at the 2025 International Liver Transplantation Society Congress in Singapore. We highlight how MP has matured into a transformative tool in liver transplantation, with growing evidence of improved graft viability, reduced complications, expanded donor utilization, and systemic impact on allocation and logistics. Special attention is given to recent innovations in translational bridges and real-world cost analyses that support broader clinical implementation.